Energy transition looming behind the headlines? Newspaper coverage of biogas production in Finland - Lyytimaki J; Nygren NA; Pulkka A; Rantala S (SPRINGER HEIDELBERG, 2022)
Background: Media coverage can play an important part in energy transitions. It creates awareness of landscape-level megatrends affecting energy systems. It influences and is influenced by public and policy agendas on a regime level. On a niche level, it can spread or screen out information and motivate or discourage actors to adopt new technologies and practices. However, relatively few studies have specifically addressed the role of media in energy transitions. Newspaper coverage of biogas is studied here as a case of media framing of a potential renewable energy solution.Methods: This article examines the long-term development of newspaper coverage of biogas in Finland. The aim of the quantitative content analysis is to draw an overall picture of the main phases of biogas coverage of a widely read newspaper focusing on agriculture and forestry, actors using discursive power in this coverage and key framings of the discussion. The results are discussed from the perspective of energy transition studies. In particular, future expectations created by the media are explored.Results: The results show a lack of newspaper coverage on biogas in the early 2000s, followed by a rapid increase and stabilisation of the volume of newspaper coverage. Biogas was most often mentioned as a secondary topic of broader discussions related to renewable energy. The core discussion focusing on biogas was characterised by very positive framings of biogas as a preferable energy solution fully compatible with the principle of circular economy. The news stories often had a strong future orientation, and examples of enthusiastic forerunners were frequently presented. However, the coverage also emphasised the poor economic profitability of biogas technologies and a need for considerable public subsidies that are inherently unpredictable.Conclusions: The future of niche-level energy technologies such as biogas can be strongly shaped by information flows, public perceptions and expectations created in part by media coverage. The analysed newspaper coverage in Finland was ambivalent from the perspective of energy transition. On the one hand, biogas production was represented as a preferable, environmentally friendly niche-level energy technology that should be encouraged. On the other hand, by emphasising the economic unviability of biogas technologies, the analysed newspaper coverage did not promote the adoption of biogas.